Reciclagem mecânica de resíduos de rótulos e etiquetas utilizando cinzas do bagaço de cana-de-açúcar - Mantovani, Guilherme Augusto (2015)
Stickers and labels communicates information about the product and displays manufacturer brand. They are usually printed on a sticker made of paper or biaxially oriented polypropylene (BOPP). Cut these labels and labels left over parings. A little label sticker manufacturer produces around of 25 ton of parings per month. The recycling of this type of material is very difficult separating and milling processes of these residues are hard tasks to be accomplished, due to the presence of a large amount of glue. This study represents an alternative method for recycling sticker residues, which contain BOPP and polyurethane glue. The residue was triturated in a knife mill with sugarcane bagasse ash. Composites were obtained from post-consumer polypropylene with different concentrations of parings/ash: 10, 30 and 50% by weight, also pure PP and 100% residue parings/ash samples. The samples were processed by extrusion and injection. These materials were analyzed by tensile, three point flexural, hardness, Izod impact, thermal analysis tests and scanning electronic microscopy (SEM). Morphological analysis indicated a good distribution of the residue in matrix. The addition of the residue parings/ash in the polypropylene matrix generated slightly more rigid material than the PP, 50% residue increased modulus of elasticity at 5,5%. The composites also had low water absorption, lower than 0.3% in 3 weeks immersed in water, and increased thermal stability. Mechanical properties were reevaluated after exposure to degradation by 60 and 120 days, was observed a little deterioration in the properties, but the equivalent pure PP losses. Therefore, from viewpoint of utilization of parings recycling process is viable. Finally, it was described the design of a pilot plant with necessary equipment for the production of the studied material.